ナンキョク ショウワキチ デ ジッシ シタ エンガン カイヨウ セイタイケイ ケンキュウ - 星合, 孝男; ホシアイ, タカオ; Hoshiai, Takao (1994)
P(論文) 国際共同研究BIOMASSの一環として実施した, 昭和基地(69° 00′S, 39° 35′E)における沿岸海洋生態系研究の結果を概説した。沿岸海洋生態系の主要構成要素に関する周年情報を得ることを目指した本研究は, 1982年から1984年にわたって行われた。植物プランクトン, アイスアルジー, 動物プランクトンについて;生産された有機粒子の沈降, 分解過程について;ナンキョクオキアミの冬期生存戦略について;底生生物の生態について;幾つかの知見が得られた。ここでは, それらの知見をとりまとめ, 紹介した。この過程を通して, 沿岸生態系を更に深く理解するためには, 未解決のまま残されている問題の研究が必要だとの感を抱くに至った。解決を要すると考えた課題は, SCARによって現在計画が進められている"Coastal and Shelf Studies in the Ecology of the Antarctic Sea Ice Zone"の枠組みの中で, 我が国の研究者が中心となって, 取り組むのにふさわしい研究だと考えている。 Results of marine biological research on the coastal marine ecosystem in the Syowa Station area (69°00′S, 39°35′E) in conjunction with BIOMASS are reviewed. This research aimed at the collection of year-round information on the basic elements in the ecosystem of the region in the 1982-84 winters. General information on the ecology of bacteria, phytoplankton, ice algae and zooplankton; sinking and decomposing processes of organic particulates produced; overwintering strategy of krill; and ecology of benthos is given. Based on the above investigations, some research topics for a recently proposed international program, "Coastal and Shelf Studies in the Ecology of the Antarctic Sea Ice Zone" were suggested. departmental bulletin paper